Human gastric carcinoma cells targeting peptide-functionalized iron oxide nanoparticles delivery for magnetic resonance imaging. (December 2020) - Chen, Weizhi; Yang, Zhongheng
Graphical abstract: Highlights: GLY-3 peptide targeting model established and fabricated to IONPs (GPC3@IONPs). The viability of the gastric SGC-7901 cells was examined by MTT assay. Further, the viability of the cells was evidenced through fluorescence staining methods. The binding ability and cellular uptake properties of naked IONPs and GPC3@IONPs were examined. Abstract: Iron oxide nanoparticles (IONPs) are broadly examined nanomaterials for their promising engagement of the progressive in biomedical application, for intense selective drug delivery and multimodal imaging. IONPs are commonly less price, and enhanced biocompatibility can be effectively functionalized with a broad range of functioning ligand, and have established to be active in improving clinical diagnostics tools and magnetic resonance imaging contrast agents. Consequently, IONPs could be used as a promising magnetic resonance imaging contrast. In this context, we have established an IONPs based framework for the multimodal in vitro imaging approach of gastric cancer cell lines that fast high level of glypican-3 protein (GLY-3) on the superficial. In this regards, a new GLY-3 peptide targeting model established and fabricated to IONPs. The aqueous property, biocompatibility profile and physical-chemical properties of the functionalized IONPs were characterised with various spectroscopical methods. The viability of the gastric SGC-7901 cells was examined by MTT assay. Further, the viability of the cells was evidenced through fluorescence staining methods. The binding ability and cellular uptake properties of naked IONPs and functionalized IONPs (GPC3@IONPs) were examined via laser scanning confocal microscopy (CLSM) in GLY-3 positive gastric cells (SGC-7901 cells). The obtained outcomes displayed that the GLY-3 functionalized IONPs remarkably improved the magnetic resonance imaging contrasts and were actively assured and occupied up by gastric cell lines without damaging the non-cancerous cells.